2015
DOI: 10.1124/jpet.115.225508
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Sodium Glucose Cotransporter 1 Inhibition Enhances Glucagon-Like Peptide-1 Secretion in Normal and Diabetic Rodents

Abstract: The sodium glucose cotransporter (SGLT) 1 plays a major role in glucose absorption and incretin hormone release in the gastrointestinal tract; however, the impact of SGLT1 inhibition on plasma glucagon-like peptide-1 (GLP-1) levels in vivo is controversial. We analyzed the effects of SGLT1 inhibitors on GLP-1 secretion in normoglycemic and hyperglycemic rodents using phloridzin, CGMI [3-(4-cyclopropylphenylmethyl)-1-(b-Dglucopyranosyl)-4-methylindole], and canagliflozin. These compounds are SGLT2 inhibitors wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
62
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 55 publications
(59 reference statements)
6
62
2
Order By: Relevance
“…Finally, an effect independent of SGLT1 inhibition might have also partially influenced the results as described above. In the current study, further elevation of plasma active GLP-1 levels was observed by addition of teneligliptin, a DPP4 inhibitor, supporting the results of previous animal studies [10,11]. This finding appears to suggest a benefit of co-treatment of canagliflozin with DPP4 inhibitors for elevating circulating GLP-1 levels.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Finally, an effect independent of SGLT1 inhibition might have also partially influenced the results as described above. In the current study, further elevation of plasma active GLP-1 levels was observed by addition of teneligliptin, a DPP4 inhibitor, supporting the results of previous animal studies [10,11]. This finding appears to suggest a benefit of co-treatment of canagliflozin with DPP4 inhibitors for elevating circulating GLP-1 levels.…”
Section: Discussionsupporting
confidence: 80%
“…Four patients in the control group and 2 in the canagliflozin-treated group retracted their written agreement on participation at least before initiation of the study (i.e., the Meal test). One patient cells located mainly in the mucosal membrane of the lower small intestine [10]. The remarkable elevation of plasma active GLP-1 levels was noted especially with co-administration of dipeptidyl peptidase 4 (DPP4) inhibitors, which block GLP-1 degradation [11].…”
Section: Originalmentioning
confidence: 99%
“…It has been previously determined that SGLT1 and GLUT2 expressions are upregulated in rats with STZ-induced diabetes. 20) Consistent with this, our DC group showed increased SGLT1 and GLUT2 gene and protein expression in the intestine, which contributes to the development of hyperglycemia. SGLT1 is transcriptionally regulated by recruiting HNF-1α and HNF-1β to the cis-regulatory element of its promoter.…”
Section: Discussionsupporting
confidence: 70%
“…The SGK1 inhibitor may also transiently inhibit SGLT1 and thereby defer and delay glucose absorption along the distal intestine (Oguma et al 2015). This effect in itself would help reduce the prandial glucose excursion and might increase GLP1 and peptide YY secretion from intestinal L cells (Oguma et al 2015). Further study is needed to investigate the effect of SGK1 inhibitors on the secretion of incretin.…”
Section: Discussionmentioning
confidence: 99%
“…This effect may be one of the mechanisms by which the SGK1 inhibitor reverses hyperglycemia in db/db mice. The SGK1 inhibitor may also transiently inhibit SGLT1 and thereby defer and delay glucose absorption along the distal intestine (Oguma et al 2015). This effect in itself would help reduce the prandial glucose excursion and might increase GLP1 and peptide YY secretion from intestinal L cells (Oguma et al 2015).…”
Section: Discussionmentioning
confidence: 99%